PERSEPSI KARYAWAN TERHADAP KETERSEDIAAN FASILITAS DAN SARANA PENANGANAN COVID-19 DI TEMPAT KERJA BERHUBUNGAN DENGAN KEPATUHAN PROTOKOL KESEHATAN - Yenni Nuriati; Ade Heryana; Intan Silviana Mustikawati; Namira Wadjir Sangadji (Jurnal Kesehatan Masyarakat (Undip), 2021)
COVID-19 is an infectious disease caused by the corona virus which has led to pandemic in all countries, especially Indonesia. The transmission of COVID-19 between humans is influenced by social interactions, for example closed contact at schools, offices and the community. In supporting business continuity in a pandemic situation, workplaces and industries are required to apply health protocols that have been stipulated in the regulations of the Indonesian Ministry of Health to control and prevent occupational related to COVID-19. The preliminary survey found that out of 10 employees, 69% of employees sometimes or never adhere to health protocols. The purpose of this study was to determine the factors related to employee compliance in implementing health protocols at office. This research used descriptive quantitative method with cross sectional design. This study involved all employees (72 samples).  Results:  The employee’s perception of a COVID-19 handling equipments is related to employee health protocols compliance (p-value < 0.001). Employee health protocol is not related to knowledge of COVID-19 (p-value = 0.347) and attitude (p value = 1.00). to increase employee compliance in the workplace, the company can provide a special officer unit that handles COVID-19 who can conduct surveillance at any time to reprimand and impose social punishment if employees do not implement heakth protocols in the workplace.